Effects of Breed, Age, Body Condition Score, and Nutritional Status on Follicular Population, Oocyte Yield, and Quality in Three Cameroonian Zebus Cattle Bos indicus - Azafack Kana Dorice; Ngoula Ferdinand; Kouamo Justin; Kenfack Augustave; Kenne Kaze Linda (Advances in Agriculture)
This study was aimed at investigating the effects of breed, age, body condition score, and nutritional status on follicular dynamics, quality, and oocyte yield in Cameroonian zebus cattle Bos indicus (Gudali and Red and White Fulani). A total of 95 cows were investigated for breed, age, body condition score, and nutritional status. Blood samples and ovaries of these cows were collected during slaughtering. Follicles on each ovary were counted and measured using electronic digital calipers and then classified into three categories: small (<3 mm), medium (3 – 8 mm), and large (> 8 mm) diameter. The oocytes were retrieved by slicing each ovary into a Petri dish containing collected medium. The oocytes recovered were examined under a stereoscope (x 10) and classified into four groups based on the morphology of cumulus oophorus cells and cytoplasmic changes. From these ovaries, 3888 follicles were counted with an average population of 27.81 ± 6.88 follicles per cow. The average numbers of small, medium, and large follicles per cow were 17.26 ± 1.36 (62.06%), 9.64 ± 1.00 (34.66%), and 0.52 ± 0.32 (1.86%), respectively. A total of 1822 oocytes were harvested with an average of 19.11 ± 0.89 oocytes per cow. Oocytes graded I, II, III, and IV were 7.03 ± 2.30 (36.65%), 4.53± 2.01 (23.61%), 3.19 ± 0.85 (16.63%), and 4.43 ±1.62 (23.09%), respectively. This study also showed that ovarian weight, number of follicles, and oocytes’ yield of right ovary were higher than left ones (P < 0.05). Younger and normal cows (BCS = 3) presented higher (P < 0.05) number of follicles and oocytes. Urea and cholesterol levels were higher in Gudali and White Fulani cows (P < 0.05). This study indicated that ovaries of zebus harvested in slaughterhouse are an important source of follicular population, oocytes yield, and quality. Right ovaries are heavy and offer more numbers of follicles and oocytes than the left ones. BCS is the best indicator of nutritional status of cows. Important follicle populations are obtained from cows aging 6-9 years with BCS = 3.